IMPLEMENTASI HIERARCHY OF NEEDS PADA KELUARGA DALAM PEMBENTUKAN KEPRIBADIAN ANAK ERA MILENIAL - Roy Bagaskara; Ahmad Putra (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
In this era social media has become a necessity in the New Life Style. Ease of access makes it increasingly loved by all circles, especially teenagers increased from 38% to 72%. However, there is often a misuse of social media by its users, this can be used as a benchmark for the internal condition of the family, lack of knowledge and supervision. However this is a big problem for millennial generation in the future because of the inaccuracy in the use of gadgets can affect cognitive, psychomotor and decreased performance. Basically all the things that are done by children are so that they can meet the five needs, namely; Physiological needs, Safety needs, Belogingness and loves needs, Estem needs, and Self-actualization needs. So that the fulfillment of all these needs can be an appropriate action in dealing with social media abuse.